Bicycle ridership and intention in a northern, low-cycling city. (October 2018) - Cabral, Laura; Kim, Amy M.; Parkins, John R.
Highlights: Planned behavior and infrastructure variables are tested to explain cycling behavior and intent. A level of traffic stress (LTS) scale is refined and supported empirically. Perceived control over time, distance, and traffic stress tolerance affect outcomes. Despite northern low-cycling context, determinants align with studies in other locales. Abstract: Cycling as a mode of transportation (i.e. utility cycling) has been given heavy attention and investment in North America over the last decade. It is perceived as an environmentally friendly way to travel, leading to benefits for health and traffic alleviation. This study examines the determinants of utility cycling behaviour and intent, and more broadly, active transportation (i.e. cycling and walking) behaviour in Edmonton, Canada – the northernmost North American city with a metropolitan population over one million. With harsh winter weather and low cycling rates, the city presents a unique case study for cycling behavior. In this research, we analyzed 646 responses to a bike ridership survey conducted in 2014 by the City of Edmonton. Borrowing concepts from behaviour theory, public health and transportation engineering we seek to quantify the effects of infrastructure density, traffic attitude, perceived control over time and distance, and traffic stress tolerance perception on cycling for utility purposes, the intention to cycle more frequently, and the use of an active mode of transportation, specifically for a northern and low-cycling city. Three empirical models were developed to describe cycling behaviour using binary logistic regression. Most variables were significant and in line with other study findings in the current literature. Results point at the importance of perceived safety in deciding or intending to cycle, as well as perceived time and distance of travel. Broad policy implications and suggestions for future research are discussed.